Alan S. Trueblood, Experience and artistic expression in Lope de Vega. The making of "La Dorotea". Harvard University Press, Cambridge, Mass., 1974; 785 pp. - Márquez Villanueva, Francisco (El Colegio de México, 1976)
Se reseñó el libro: Experience and artistic expression in Lope de Vega. The making of "La Dorotea".